The Effectiveness of The Marmet Technique Breast Massage is Comparable to Standard Breast Massage - Oktaviani, Ika; Aliyanto, Warjidin (Poltekkes Kemenkes Tanjung Karang, 2023)
Exclusive breastfeeding is essential for human infants' physical and mental development. However, breastfeeding problems can hamper this low quantity of breast milk. This study aimed to evaluate the benefits of Marmet breast massage for increasing the amount of breast milk in post-partum mothers. This is an experimental study design. The subjects of 100 breastfeeding mothers were randomly assigned to two groups; a control group (which received standard breast care massage) and the treatment group (who received the Marmet technique breast massage). Although there were no significant differences in the rate of change over time between the Marmet technique group and the control group (p-value>0.05), there was an increase in breastfeeding fluency scores in the Marmet technique group. The Marmet breast massage technique increased milk production in term infants at a rate comparable to usual breast massage. Therefore, this technique could be used to improve exclusive breastfeeding rates, including for mothers with nipple abnormalities.